Metal oxide alternatives for efficient electron transport in perovskite solar cells: beyond TiO2 and SnO2. Issue 38 (25th September 2020) - Cao, Zhiyuan; Li, Chengbo; Deng, Xiaoyu; Wang, Shurong; Yuan, Yuan; Chen, Yuanming; Wang, Zhi; Liu, Yaqing; Ding, Liming; Hao, Feng
Abstract : Recent advances of metal oxides beyond TiO2 and SnO2 for electron transport in perovskite solar cells are reviewed from the aspects of nanostructuring, element doping, surface modification, multi-layer design and large-scale fabrication. Abstract : Carrier transport layers have been recognized as a key factor to determine the performance of perovskite solar cells (PSCs) by dominating the charge carrier extraction, transport and recombination process. Metal oxides have been widely used as electron transport layers (ETLs) in PSCs for high performance and stability, of which TiO2 and SnO2 are the most popular choices. However, the large-scale implementation of TiO2 and SnO2 ETLs is hindered by their own deficiencies, such as low electron mobility, poor stability against UV light and surface defects. Therefore, binary and ternary metal oxide alternatives have been widely investigated recently. Here, we review the recent advances of these metal oxide ETLs in PSCs with a special focus on the nanostructuring, elemental doping, surface modification, and multi-layer ETLs and large-scale fabrication of these ETLs. Furthermore, the state-of-the-art progress towards high-efficiency and stable PSCs using these novel ETLs is summarized and future perspectives are discussed.